INTEGRASI NILAI-NILAI KEJUJURAN SEBAGAI WUJUD PENDIDIKAN ANTI KORUPSI DI SEKOLAH DASAR NEGERI TENGKLIK KABUPATEN KARANGANYAR - Nadziroh Nadziroh; Chairiyah Chairiyah; Wachid Pratomo (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
This study aims to determine the implementation of honesty valuesÂ as a form of anti-corruption education in SD Negeri 01 Tengklik Karanganyar. The results showed that in Tengklik 01 Public Elementary School had carried out honesty values as a form of anti-corruption education. The anti-corruption valuesÂ taught in Tengklik 01 Public Elementary School include the value of honesty, the value of discipline, the value of openness, and the value of responsibility. Inhibiting factors or constraints are: (1) lack of awareness of students, (2) there are still habits of corruptive behavior. There are several ways that can be used to overcome obstacles and efforts made in Anti-Corruption Education, namely: (1) exemplary, (2) habituation, (3) giving strict sanctions. (4) competitions and resource persons (5) increasing devotion.